2023
DOI: 10.1039/d2qi02634a
|View full text |Cite
|
Sign up to set email alerts
|

Halogen bonding between metal-bound I3 and unbound I2: the trapped I2⋯I3 intermediate in the controlled assembly of copper(i)-based polyiodides

Abstract: Crystallization of [CuI(CNXyl)3] (1) with I2 (exhibiting strong halogen bond donor properties), at different molar ratios between the reactants, resulted in a series of (XylNC)CuI crystal polyiodides formed along with...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 78 publications
(149 reference statements)
0
9
0
Order By: Relevance
“…In view of our interest in the chemistry of dialkylcyanamides and also in crystal engineering involving coinage metal complexes, we attempted to crystallize CuI with the dialkylcyanamides NCNR 2 (R 2 = Me 2 , Et 2 , C 4 H 8 , C 5 H 10 , C 4 H 8 O) in the presence of such mixed σ-/π-hole donors as 1,4-FIB or 1,4-FBrB. Despite our repeated attempts, only experiments with the system CuI/NCNMe 2 /halo­(perfluoro)­arenes in MeCN gave cocrystals 1 ·1,4-FIB, 2 ·1,4-FIB, and 1 ·1,4-FBrB; they all were studied by XRD.…”
Section: Resultsmentioning
confidence: 99%
“…In view of our interest in the chemistry of dialkylcyanamides and also in crystal engineering involving coinage metal complexes, we attempted to crystallize CuI with the dialkylcyanamides NCNR 2 (R 2 = Me 2 , Et 2 , C 4 H 8 , C 5 H 10 , C 4 H 8 O) in the presence of such mixed σ-/π-hole donors as 1,4-FIB or 1,4-FBrB. Despite our repeated attempts, only experiments with the system CuI/NCNMe 2 /halo­(perfluoro)­arenes in MeCN gave cocrystals 1 ·1,4-FIB, 2 ·1,4-FIB, and 1 ·1,4-FBrB; they all were studied by XRD.…”
Section: Resultsmentioning
confidence: 99%
“…Although strong π-back-donating isocyanide ligands similar to other complexes of low-oxidation state metal centers are able to stabilize the copper­(I) oxidation state, (RNC)­Cu I -based polyhalides are still little explored. We recently obtained the polyhalide adducts [Cu­(I 3 )­(CNXyl) 3 ], [Cu­(I 3 )­(CNXyl) 3 ]· 1 / 2 I 2 , and [Cu­(CNXyl) 3 ]­(I 5 ) from [CuI­(CNXyl) 3 ] and I 2 ; these species are formed depending on the molar ratio between the reactants . In view of our interest in isocyanide chemistry (for review, see ref ; for recent works, see refs and and references therein), copper­(I) chemistry, and the supramolecular chemistry of polyhalides (for recent works, see refs , , and ), the idea of a study that combines all three areas seemed to be attractive.…”
Section: Resultsmentioning
confidence: 99%
“…In line with our general interest to noncovalent interactions and in particular toward metal-involving interactions (for recent reports, see refs and references therein), we studied self-association of thiocyanate Pd II ( 3 ) and Pt II ( 4 ) complexes (Scheme ). We found that 3 and 4 form isomorphous crystals, where these metal species are assembled in 1D supramolecular polymer primarily by M···S noncovalent interactions.…”
Section: Introductionmentioning
confidence: 99%